Pengaruh Konsentrasi Ekstrak Daun Kersen (Muntingia Calabura L.) Terhadap Hambatan Pertumbuhan Enterococcus faecalis Dominan Pada Saluran Akar Secara In Vitro - Jatiningrum, Jatiningrum; , drg.Mahmud Kholifa, MDSc; , drg.Fitria Nurmalita Sari (2016)
Root canal treatment is a treatment for pulp diseases that done by taking the entire of necrosis pulp tissue. The main caused of failure root canal treatment was the stage of irrigation that unfavorable. 2% Chlorhexidine is a chemical material irrigation of root canal. Chlorhexidine has disadvantages such as allergic reactions and discoloration of teeth, therefore the study research of material which did not have side effect should be done. Cherry (Muntingiacalabura L.) is a plant that the leaves believed to inhibit the growth of bacteria because they contain active substances like flavonoids, tannins and saponins. This study was aimed to investigate the effect of concentration cherry leaves extract (Muntingiacalabura L.) and know which concentration that has the highest barriers to inhibit the growth of Enteroccocus faecalis. This experimental laboratory study used 5 treatment groups were 15%, 30%, 60% concentration of cherry leaves extract (Muntingiacalabura L.), a sterile distilled water as a negative control, 2% chlorhexidine as a positive control, then replicated 5 times. The research used Kirby bauser method and incubation with 37˚C temperature for 24 hours. Inhibition zone will be seen, then measured using a caliper to millimeters. Research showed that cherry leaves extract (Muntingiacalabura L.) has antibacterial activity against Enterococcus faecalis on concentration of 15% (d=10.62 mm), 30% (d=13.43 mm) and 60% (d=17.71 mm). The result of one way Anova showed the significance value p = 0.000 (p <0.05), so it can be concluded that cherry leaves extract (Muntingiacalabura L.) has the effect on Enterococcus faecalis growth inhibition and cherry leaves extract of 60% concentration has the highest barriers.